2018
DOI: 10.17576/gema-2018-1804-15
|View full text |Cite
|
Sign up to set email alerts
|

Delikuidasi Kata Pinjaman Arab dalam Dialek Kelantan (Deliquidation of Arabic Loanwords in Kelantan Dialect)

Abstract: Modifikasi fonologi sering berlaku ke atas fonem asing dalam kata pinjaman. Lazimnya, fonem asing akan digantikan dengan fonem natif yang paling hampir. Hal ini kerana setiap bahasa mempunyai peraturan tentang penyusunan onset, nukleus dan koda serta mempunyai sistem fonotaktik tersendiri. Oleh itu, kajian ini bertujuan melihat isu kata pinjaman bahasa Arab dalam dialek Kelantan dengan memfokuskan kepada modifikasi fonologi yang dominan, iaitu proses delikuidasi. Delikuidasi merujuk kepada proses fonologi peng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(9 reference statements)
3
0
0
Order By: Relevance
“…Adelaar [67] and Abdul Aziz [68] described the final /s/ substitution by /h/. Their finding is similar to our observation, where the final SM letter 's' is substituted with letter 'h' in KD (refer to Table 12, item 1).…”
Section: Deletion Of Consonants In Word-final Positionsupporting
confidence: 89%
See 2 more Smart Citations
“…Adelaar [67] and Abdul Aziz [68] described the final /s/ substitution by /h/. Their finding is similar to our observation, where the final SM letter 's' is substituted with letter 'h' in KD (refer to Table 12, item 1).…”
Section: Deletion Of Consonants In Word-final Positionsupporting
confidence: 89%
“…Brown et al [73] recorded 19 languages that have the correspondence /s/ > /h/. Besides the final /s/ substitution, Abdul Aziz [68] also reported that the consonant deletion in the final phoneme /l/ and /r/. This observation is similar to our finding, where SM words with the final letter 'l' and 'r' are deleted in KD.…”
Section: Deletion Of Consonants In Word-final Positionsupporting
confidence: 89%
See 1 more Smart Citation